2009
DOI: 10.1590/s1676-06032009000200024
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome number and microsporogenesis of two accessions of Brachiaria dura Stapf (Poaceae)

Abstract: The two accessions of B. dura analyzed (DU01 and DU02) are hexaploid (2n = 6x = 54), derived from x = 9. Meiotic abnormalities, such as precocious chromosome migration to the poles, laggards and micronuclei, were recorded in low frequency in both accessions. The few multivalent chromosome association at diakinesis and meiotic stability suggested that hexaploidy probably resulted from chromosome doubling. In DU02, chromosome transfer (cytomixis) among meiocytes, involving part or the entire genome was observed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Micronuclei were also eliminated as microcytes (Figure 1j, k, l). The same type of behavior was reported in polyploid accessions of B. brizantha (Mendes-Bonato et al, 2002;RissoPascotto et al, 2003), B. nigropedata (Utsunomiya et al, 2005), B. jubata , B. dictyoneura (Risso-Pascotto et al, 2006a), B. dura (Risso-Pascotto et al, 2009a), and B. bovonei and B. subulifolia (Risso-Pascotto et al, 2009b). Irregular chromosome segregation compromises pollen fertility by producing unbalanced microspores.…”
Section: Resultssupporting
confidence: 56%
“…Micronuclei were also eliminated as microcytes (Figure 1j, k, l). The same type of behavior was reported in polyploid accessions of B. brizantha (Mendes-Bonato et al, 2002;RissoPascotto et al, 2003), B. nigropedata (Utsunomiya et al, 2005), B. jubata , B. dictyoneura (Risso-Pascotto et al, 2006a), B. dura (Risso-Pascotto et al, 2009a), and B. bovonei and B. subulifolia (Risso-Pascotto et al, 2009b). Irregular chromosome segregation compromises pollen fertility by producing unbalanced microspores.…”
Section: Resultssupporting
confidence: 56%
“…The genus Saccharum is well-known for its exclusively higher-order polyploid species, such as S. officinarum, S. robustum and S. spontaneum, the latter two with variable chromosome numbers or cytotypes. In this study, we confirmed that S. officinarum exhibits a relatively low number of meiotic abnormalities (~6%), i.e., regular meiosis, similar to that of other polyploids in the grass family (Leofanti et al 2017;Aissat et al 2019;Risso-Pascotto et al 2003). In contrast to our findings, these studies report abnormalities higher than 30%.…”
Section: Discussionsupporting
confidence: 81%
“…Brachiaria mutica and Brachiaria arrecta are tetraploidal species; the first exhibits irregular chromosome pairing and reproduction by apomixis, and the latter exhibits fairly regular bivalent pairing and sexual reproduction (Valle, 1986). Risso-Pascotto et al (2009a) observed meiotic abnormalities at a low frequency in two hexaploid accessions of Brachiaria dura, as well as a few multivalent chromosome associations at diakinesis, and suggested that hexaploidy probably resulted from chromosome doubling. The accumulated evidence from several studies on Brachiaria point to an association between polyploidy and apomixis, with irregular meiosis, on the one hand, and sexual reproduction and regular chromosome pairing on the other (Valle and Savidan, 1996;Valle and Pagliarini, 2009).…”
Section: Discussionmentioning
confidence: 96%